Seroprevalence of syphilis among women attending urban antenatal clinics in Burkina Faso, 1995–8. Issue 4 (1st August 2000) - Sombié, I; Meda, N; Cartoux, M; Tiendrébéogo, S; Ouangré, A; Yaro, S; Ky-Zerbo, O; Dao, B; Van de Perre, P; Mandelbrot, L; Dabis, F
Abstract : Objectives: To describe annual trends in syphilis seroprevalence and to identify risk factors of syphilis among pregnant women receiving antenatal care in Bobo-Dioulasso, Burkina Faso. Methods: Women were recruited between January 1995 and July 1998 in three antenatal clinics where counselling and HIV testing services had been established in the context of a trial evaluating a short course of zidovudine to reduce mother to child transmission of HIV (ANRS 049 trial). Sociodemographic variables were collected during HIV pretest counselling sessions. Syphilis diagnosis was considered when serum was positive with both rapid plasma reagin and Treponema pallidum haemagglutination assay (TPHA) tests. Results: Overall, 10 980 pregnant women were screened. Syphilis seroprevalence was 0.24% (95% confidence interval (CI): 0.15–0.35) without changes over time. HIV prevalence was 8.8% (CI: 8.3–9.3). In a multivariable analysis, having casual sex partners (odds ratio (OR) = 4.48; CI: 1.62–12.38), being HIV seropositive (OR = 2.62; CI: 1.02–6.74), and being illiterate (OR = 3.78; CI: 1.24–11.48) were independent risk factors for syphilis infection. Conclusions: This study suggests low syphilis seroprevalence in this city of Burkina Faso. Sexually transmitted disease programmes should be reinforced to offer free access to syphilis screening and treatment in order to eliminate this disease, in coordination with HIV prevention and care.